Competitive entry strategies in overseas marketing of construction export - Munukutla, V. Rao. (2009)
Since the late eighties, world economic growth has focussed on the Asia Pacific Region. Many countries in this region have been registering strong growth and this trend is set to continue well into the next century. The Construction Industry Development Board estimates the Region's construction demand at more than US Dollar 1 trillion each year for the next few years. So vast is the potential that Singapore construction firms cannot afford to ignore. This research report addresses the various opportunities available for Singapore contractors in the Region.